2019
DOI: 10.1109/tbme.2019.2900002
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Layer Gaussian Process for Motor Symptom Estimation in People With Parkinson's Disease

Abstract: The assessment of Parkinson's disease (PD) poses a significant challenge as it is influenced by various factors which lead to a complex and fluctuating symptom manifestation. Thus, a frequent and objective PD assessment is highly valuable for effective health management of people with Parkinson's disease (PwP). Here, we propose a method for monitoring PwP by stochastically modeling the relationships between their wrist movements during unscripted daily activities and corresponding annotations about clinical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Second, these authors used unsupervised cluster analysis to categorize each time point of the spectrum into one of 20 behaviour groups (Sakamoto et al, 2009). In human patients with Parkinson's disease, Lang et al (2019) showed behaviours, such as sitting and standing, appear in accelerometer recording of wrist movement as periodic at a different frequency than tremors. Thus, authors used wavelet analysis as a processing step for modelling the relationships between wrist movements during daily activities and clinical displays of movement abnormalities (Lang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, these authors used unsupervised cluster analysis to categorize each time point of the spectrum into one of 20 behaviour groups (Sakamoto et al, 2009). In human patients with Parkinson's disease, Lang et al (2019) showed behaviours, such as sitting and standing, appear in accelerometer recording of wrist movement as periodic at a different frequency than tremors. Thus, authors used wavelet analysis as a processing step for modelling the relationships between wrist movements during daily activities and clinical displays of movement abnormalities (Lang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chimienti et al (2022) showed, in two penguin species, that by using a large sample size and including behavioural variability within training datasets resulted in a high level of accuracy (>80%) between the supervised and unsupervised approaches. The detection of tremors in Parkinson's patients with multi-layer Gaussian process prediction models showed an accuracy of 83% (Lang et al, 2019). Support vector machine (SVM) algorithms have shown overall mean accuracies between 80% and 87% and, when reported, a sensitivity of around 80% for classifying behavioural events correctly from acceleration data in different species such as penguins (Carroll et al, 2014), cows (Martiskainen et al, 2009) and broilers (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have explored the use of machine learning to automatically detect PD motor symptoms with wearable sensor [ 9 , 10 , 11 ], considering several motor symptoms at the same time in several cases [ 12 ]. Despite this strong interest, there are no commercial systems that provide a good user experience or sufficient accuracy to complement doctor assessments.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, multiple methods such as joint time-frequency analysis, statistical analysis, and machine learning have been employed to study the tremor so far. Spectral analysis and time-frequency analysis were well utilized in several previous studies [18,19]. Salarian et al [20] used frequency and amplitude of the signals to detect and quantify resting tremor through fixed thresholding.…”
Section: Introductionmentioning
confidence: 99%